Influence of Maturity and Vineyard Location on Free and Bound Aroma Compounds of Grapes from the País Cultivar - Ubeda, C.; Gil i Cortiella, M.; Del Barrio Galán, R.; Peña-Neira, A. (South African Journal of Enology and Viticulture, 2017)
Some of the volatile compounds present in grapes give wine is its unique and genuine characteristics. “Terroir” and berry maturity are considered to be the main influences on the expression of these characteristics. This work was undertaken to establish the specific characteristics that define Vitis vinifera cv. País, based on its aromatic profile and free and bound compounds (glycosides), and to assess the effects of location and maturity. Free and bound volatile compounds presented significant differences in the three locations studied. The total amount of free alcohols, acids and ketones depended on the location. During ripening, the amount of aroma precursors increased in all chemical groups in every location studied, and they were found mainly in the skins. With reference to free volatile compounds, it was found that cis-2-hexenol could be a good candidate to assess maturity, and that terpene content seemed to be strongly related to the vineyard location and cultivar conditions. Also, data analysis showed that the free aroma profile seemed to be influenced more by the maturity of the grapes and the bound aroma fraction more by the location.